Child labor in India - should It be legalized? - Saha, Sampa (KDI School, 2012)
It is a fact that child labor is a crucial issue that is prevalent in different parts of the world for ages, even in the developed nations. Though there is a claim that there are number of activities going on, all around the world to combat this deadly disease, in reality it is seen that only a little is achieved towards the mission of eradication. The Indian scenario of the child labor is painful as India is the country having the largest number of working children in between 5 to 14 years of age and with the second highest population in the world, there is as little chance to curb child labor, in the way the actions are taken. To follow the guidelines of ILO, India has adapted measures those are practically undoable when India is plagued with poverty, illiteracy and population growth. To have a sustainable strategy towards reduction of child labor and to make the children’s future dignified this paper searches for a practical strategy that is workable in Indian scenario of culture and social structure. If the present way of handling it, were the correct way to eradicate, it would have been abolished by this time and could not have continued for hundreds of years. There are many loopholes in the present regulations and there is social hindrances that restricts the efforts to curb child labor. It seems that the if the laws are modified so that the child labor issue is legalized to have a better effect of children’s work on their future , it will help the society to curb child labor in a phased manner. By providing mandatory education and nutrition facilities by the employers, it will be possible to get future adults healthy and educated. So the next generation can have skilled and educated parents. Thus there is possibility of curbing it through a different approach of legalization, instead of trying to curb in an abrupt and impractical manner.
Thesis(Master) --KDI School:Master of Public Policy,2012